Use of compounds in scientific texts - Frolova, Y. (KAZGUU Liberal Arts Digest Volume 4. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
Compounds is one of the most popular word types in the English language and scientific style in particular. This article is dedicated to the problem of practical classification of compounds in the texts of scientific register. It focuses on four par ticular frameworks based on such criteria as part of speech, compliance of word se mantics and constituent semantics, remainders of syntactic structure, intermediary segment and formation of constituents. The choice of the method used fell on the qualitative method of content frequencies analysis used for linguistic researches. With the help of this method, the most frequently found compound type found has been nominal, fully motivated, asyntactic, morphological compound. This pattern has been linked to such scientific style features as nominalization, semantic clarity, and concise character. Thus, compounds met appeared to reflect some distinctive peculiarities of scientific register, which has been implied from predominant types in classifications
Keywords: compounds, Bloomfield, Antrushina, Arnold